Healthy Food Education Affects Underweight Adolescent's Knowledge and Intakes of Energy, Macro and Micro Nutrients - Mustafa, Annasari; -Sutjiati, Endang; Agustin, Sheily Inge (Poltekita : Jurnal Ilmu Kesehatan, 2023)
One of the causes of underweight is an imbalance between nutritional intake and needs. The condition often occurs in teenagers and in Indonesia there are 8.1%. This study aims to investigate the impact of healthy diet education delivered by peers on the level of knowledge; energy, macro and micro nutrients intake among underweight adolescents at state Senior High School 1 in Singosari, Malang Regency. This study conducted on 33 undeweight adolescent’s girls selected based on inclusion criteria. Data collection was carried out before and after the intervention. Adolescents’ nutritional knowledge was collected by asking questions using Google forms and food consumption data collection was carried out by direct interviews using a 24-hour food recall form. The intervention took the form of education and guidance from peer tutors when the subjects consumed snacks and lunch at school, which was carried out 14 times, 2 times a week during 8 weeks. The effect of providing education on the level of knowledge; Energy, carbohydrate, protein, fat and zinc intake were analyzed using the paired sample t test, while vitamin C and iron intake used the Wilcoxon test (95% CI; α = 0.05).The results showed significant improvements in the level of knowledge intake of Energy, Protein, Fat, Carbohydrates as well as Iron and Zinc (p-value <0.05), while the increase in vitamin C intake was not significantly different (p-value >0.05). These findings demonstrated the potential of providing healthy diet education by peers to increase knowledge, energy, macro and micro nutrient intake among underweight adolescent girls.